Active cooling and low carbon comfort. Issue 3 (2nd April 2016) - Winter, Tim
Abstract : Within the debate about fostering more sustainable built environments one of the key battlegrounds surrounds thermal comfort, and in particular the use of air conditioning. In the search for less energy-intensive alternatives, a renewed interest has emerged around the design vocabulary of 'passive cooling'. The paper argues that the terminology of passive/active needs inverting for such approaches to gain wider support as a viable alternative to mechanical cooling. It is argued that non-air-conditioned buildings actively engage with their environments and that the current notion of passive cooling leaves us blind to the ways occupants, buildings and the material culture of interior spaces are all entangled in relations that enable thermal comfort to be actively achieved and maintained. To present this argument for re-categorising low-carbon architecture design as active cooling, the paper draws on the concept of entanglement.